Athlete`s blood: sport category specific hematological adaptations in a large cohort of Olympic athletes - Di Gioia, G.; Ferrera, A.; Serdoz, A.; Zampaglione, D.; Fiore, R.; Spinelli, A.; Lemme, E.; Squeo, M. R. (Sport Sciences for Health, 2025)
Background Regular physical activity and training induce physiological and metabolic adaptations that impact sports performance and overall health. Blood biomarkers serve as indicators for assessing training effects and detecting abnormalities in athletes.